Investigating The Importance Of Cultural Awareness In EFL Learning. Case Study Third Year English Students at Mohamed Cherif Messadia. Souk Ahras. - Charmati Khaoula (My University, 2022)
Abstract For many years English language teachers (ELT) attention revolved mainly around teaching language conventions ignoring the communicative aspect of language learning. Despite the fact that, the primary objective of learning a foreign language is enabling the learners to converse adequately with native speakers of the target language. Accordingly, the present dissertation investigates the importance of cultural awareness in EFL classes at the English Department, at the university of Souk Ahras. It aspires at highlighting the need to be culturally aware of the target language in order to facilitate the learning process of EFL learners. To execute our research, qualitative and quantitative approaches were adopted, and in order to collect data we opt for a questionnaire that was addressed to Third year students at the university of Souk Ahras, in addition to a structured interview which was coordinated with (06) teachers of English from the same department After that, the responses are categorized and statistically and subjectively analyzed. The findings revealed that teachers and the majority of students are aware of the impact of TC on language learning since it can improve students' achievement and mastery of the target language. Moreover, according to the findings, culture incorporation in learners' instruction boosts their learning process the more they are aware of the culture of language the more they would like to learn, discover, and practice the language pushing them to develop their skills. furthermore, culture influences the outcomes of learners so the one who shows willingness and greediness to know the other culture learn in adequate way. Finally, the researcher can confirm the hypothesis after analyzing the data acquired from the research instruments used, and based on the findings, make a number of recommendations aimed at improving the implementation of culture in third-year English classrooms.